Tests on a Small Rainfall Simulator for Evaluating Soil Erodibility - Wan Harun, Wan Sulaiman; Marsom, Isnan; A. Manan, Mohd. Mokhtaruddin (1990)
A selected number of upland soils were subjected, in situ, to simulated rain of short duration in order to establish a methodology for evaluating erodibility of Malaysian soils. The rainfall simulator produces an 18mm shower in three minutes from an average height of OAm, falling onto a 0.0625m2 test plot area at 20% slope. Results from both the surface and sub-surface horizons show less variability in the soil loss between plots than between successive runs on the same plot. Mean soil loss ranged between 5A2g and 12. 66g per plot. Soil loss was found to be not very sensitive to small variations in antecedent soil moisture around the field capacity value. The method appears capable of discriminating responses between soils and is thus, suited to the study of erodibility of upland soils in Malaysia.